(untitled) (Minerva, 2019)
This paper aims at analysing two speeches, one in latin and the other in greek, dedicated to emperor Julian (331-363 A.D.) at the outset of Consulate years 362 and 363, with a common rethoric pattern. My study will focus on the shared elements from the propagandistic Julian’s writtings and the way they evolve over this short period of time.